1996
DOI: 10.5144/0256-4947.1996.33
|View full text |Cite
|
Sign up to set email alerts
|

Drug Overdose in the Asir Region of Saudi Arabia

Abstract: Fifty-seven cases of drug overdose, seen in Asir Central Hospital, Abha, Saudi Arabia, during the period from 1989 to 1993 inclusive were studied. The study has shown progressive increase in the number of parasuicides in recent years. Forty-six cases were diagnosed as self-induced drug overdose (parasuicide), while the remaining 11 were considered to be accidental overdose, mainly in children. The sociodemographic features of the sample showed that 89% of the parasuicide cases were among Saudis and that 77.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…While these data do not clearly separate those which were accidental from those that were deliberate, the conclusion reached was that a significant portion for this number were indeed intentional. Similar trends have been reported in Saudi Arabia (Malik et al . 1996), Kuwait (Al‐Ansari et al .…”
Section: Introductionsupporting
confidence: 90%
“…While these data do not clearly separate those which were accidental from those that were deliberate, the conclusion reached was that a significant portion for this number were indeed intentional. Similar trends have been reported in Saudi Arabia (Malik et al . 1996), Kuwait (Al‐Ansari et al .…”
Section: Introductionsupporting
confidence: 90%
“…While these data do not clearly separate those that were accidental from those that were deliberate, the conclusion reached was that a signifi cant portion of this number was indeed intentional (8) . Similar trends have been reported in Saudi Arabia, Kuwait and Bahrain (9,10) . Some authors have suggested that the rise in self-harm behavior is in part because of the cultural stress inherent in rapid modernization, as well as social destabilization and poverty (3) .…”
Section: Introductionsupporting
confidence: 88%
“…Another finding in our study shows that the most common drug overdose was for analgesic and non-steroidal anti-inflammatory drugs 23 (29.49%), similar to another study conducted in Asir Region in Saudi Arabia in 1995 [ 11 ]. We assume that the reason for the similarity is due to the same demographic and cultural study sample.…”
Section: Discussionsupporting
confidence: 89%